Development of an Environmental Management Model based on Community Way of Life For Enhancng Community Excellence of Sustainable Environmental Literacy in Pathumthani Province - Jaidee, Nayiga; Buachan, Karnjanawan; Suwannawong, Yodchai (Journal of Health Science of Thailand, 2020)
The aims of this mixed-method research were to study the components of community excellence of sustainable environmental literacy and develop an environmental management model based on community way of life for enhancing community excellence of sustainable environmental literacy in Pathumthani Province. It was conducted during March to August 2019. The samples consisted of experts and the individuals working in community environmental work in Pathumthani Province, selected by the purposive sampling technique. Semi-structured interview and questionnaire schedule was constructed and used as tool for data collection; and the data were analyzed by using descriptive statistics and content Analysis. It was found that the components of community excellence of sustainable environmental literacy were (1) community data base, (2) the media and learning center, (3) regular community environment activities, 4) environment network, and (5) environment management model. The environmental management model based on community way of life for enhancing community excellence of sustainable environmental literacy in Pathumthani Province consisted of 5 complements: (1) concepts: mindset and local wisdom; (2) principles: promotion of awareness, learning and participation; (3) goals: environment literacy, environment sustainability; (4) process: social trend, community awareness, resource and community learning, public meeting, community participation, and best practice; and (5) evaluation: self-reliance/ stainable community, community literacy, and environment network. The model was considered highly appropriate in promoting community excellence of sustainable environmental literacy in Pathumthani Province (Mean=3.54, SD=0.574); and the model could be applied to the context of the society in the province (Mean=3.41, SD=0.875). There were 2 factors that could positively affect environmental management model based on community way of life: (1) existing environmental volunteer in community, and (2) availability of technologies to supporting community learning.